Robotic assisted milling for increased productivity. Issue 1 (2018) - Ozturk, E.; Barrios, A.; Sun, C.; Rajabi, S.; Munoa, J.
Abstract: Robots' role in machining is growing as they are being used as machining platforms in increasing number of applications. Moreover, robots have an important role in a new application called, robotic assisted milling, where a robot provides additional support to a workpiece when actual machining is performed by a machine tool. In the paper, alternative methods of support with the robot, i.e. fixed and mobile support are explained. Experimental results show that the robot's support improves the static and dynamic response of the process. Hence, dimensional errors are minimized and surface quality is improved.